New Target Regions for Human Hypertension via Comparative Genomics - Stoll, Monika; Kwitek-Black, Anne E.; Cowley, Allen W.; Harris, Eugenie L.; Harrap, Stephen B.; Krieger, José E.; Printz, Morton P.; Provoost, Abraham P.; Sassard, Jean; Jacob, Howard J. (Genome Research, 2000)
Models of human disease have long been used to understand the basic pathophysiology of disease and to facilitate the discovery of new therapeutics. However, as long as models have been used there have been debates about the utility of these models and their ability to mimic clinical disease at the phenotypic level. The application of genetic studies to both humans and model systems allows for a new paradigm, whereby a novel comparative genomics strategy combined with phenotypic correlates can be used to bridge between clinical relevance and model utility. This study presents a comparative genomic map for “candidate hypertension loci in humans” based on translating QTLs between rat and human, predicting 26 chromosomal regions in the human genome that are very likely to harbor hypertension genes. The predictive power appears robust, as several of these regions have also been implicated in mouse, suggesting that these regions represent primary targets for the development of SNPs for linkage disequilibrium testing in humans and/or provide a means to select specific models for additional functional studies and the development of new therapeutics.